2003
DOI: 10.1113/jphysiol.2002.038117
|View full text |Cite
|
Sign up to set email alerts
|

Troponin I in the murine myocardium: influence on length-dependent activation and interfilament spacing

Abstract: Cyclic AMP-dependent protein kinase (PKA) targets contractile proteins, troponin-I (TnI) and myosin binding protein C (MyBP-C) in the heart and induces a decrease in myofilament Ca2+ sensitivity. Yet, the effect of sarcomere length (SL) change on Ca2+ sensitivity (length-dependent activation: LDA) following PKA-dependent phosphorylation is not clear. To clarify the role of PKA-dependent phosphorylation of TnI and MyBP-C on LDA in the heart, we examined LDA in skinned myocytes from a non-transgenic (NTG) and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
86
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 57 publications
12
86
2
Order By: Relevance
“…This important cellular mechanism can be modulated by fine tuning myofilament Ca 2+ sensitivity at the molecular level, in part through dynamic post-translational modifications (PTMs) to cTnI. Importantly, these modifications to cTnI and other thin and thick filament proteins collectively serve to regulate myofilament contraction and relaxation [11,12]. The counterweights to physiological cTnI modifications are maladaptive and disease-induced modifications that can adversely affect contractility.…”
Section: Introductionmentioning
confidence: 99%
“…This important cellular mechanism can be modulated by fine tuning myofilament Ca 2+ sensitivity at the molecular level, in part through dynamic post-translational modifications (PTMs) to cTnI. Importantly, these modifications to cTnI and other thin and thick filament proteins collectively serve to regulate myofilament contraction and relaxation [11,12]. The counterweights to physiological cTnI modifications are maladaptive and disease-induced modifications that can adversely affect contractility.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the myofilament Ca 2+ sensitivity changes as a result of phosphorylation of the myofilament proteins, not only in pathological conditions as a result of adaptation or maladaptation, but also during physiological conditions such as exercise 50 . Several in vitro studies have shown that phosphorylation of TnI by PKA can shift the myofilament Ca 2+ sensitivity as much as 0.2 pCa units 46,51 , suggesting that similar changes occur in vivo . Also, we have previously shown that another TG mouse model of HCM with the mutation D175N in Tm, which shows a small relative increase of myofilament sensitivity to Ca 2+ , also demonstrates only a small relative degree of diastolic dysfunction and almost no hypertrophy 52 .…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, our goal was to desensitize the myofilaments without altering the expression of mutated Tm to make the studies more clinically relevant and as a proof of concept that treatment of HCM with desensitizers should be considered as a potential new treatment. TnI has been recognized as an important regulatory protein for Ca 2+ -mediated thin filament activation 44,45 and furthermore, phosphorylation of TnI at Ser-23/24 reduces the myofilament Ca 2+ sensitivity 46,47 . This makes TnI an excellent potential target for the development of Ca 2+ desensitizers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the series of experimental findings by the de Tombe group [5557] suggests that the lattice spacing does not solely determine the magnitude of length-dependent activation, and it does not rule out the involvement of the lattice spacing in the regulation of length-dependent activation.…”
Section: Titin’s Role As a Modulator Of Interfilament Lattice Spacingmentioning
confidence: 99%